Economic Stimuli from the Ministry of Culture of Peru: The Best Way to Promote Economic Growth in Peru's Creative Industries? - Bullard, Ines (2023)
The article examines Peru’s Ministry of Culture’s economic stimulus mechanism as a catalyst for cultural growth. It breaks down its functioning, emphasizing it’s support for independent projects, diversity, and innovation. Challenges like complex application processes are addressed, with potential solutions. It also explores the option of subsidizing cultural demand over supply, democratizing access, attracting new audiences, fostering diverse experiences, erasing economic barriers, and empowering consumers. In conclusion, the article underscores the significance of economic stimuli and demand-side policies, calling for enhancements to enrich Peru’s inclusive and diverse cultural landscape.